PEMBINAAN WARGA GEREJA SEBAGAI SARANA PENGUATAN NILAI MORAL DAN ETIKA KRISTEN DI ERA DIGITAL - Semry Tafuli (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2026)
Moral decline and ethical crises in the digital era have become serious challenges for society, including church communities. The rapid advancement of digital technology has brought significant changes to lifestyles, patterns of interaction, and the formation of human character. On the one hand, technology offers various conveniences; on the other hand, it also gives rise to ethical issues such as individualism, hedonism, misuse of social media, cyberbullying, digital pornography, the spread of hoaxes, and the erosion of moral integrity. These conditions highlight the importance of the church’s role in providing church member development that is capable of strengthening Christian moral and ethical values in a contextual and sustainable manner. This study aims to analyze the role of church member development as a means of strengthening Christian morality and ethics amid the challenges of the digital era. The research employed a descriptive qualitative approach with literature study as the primary data collection technique. Data were obtained through the examination of scientific journals and various relevant literature concerning church development, Christian ethics, and moral challenges in the digital era. The findings indicate that church member development plays a strategic role in fostering spiritual maturity, strengthening moral integrity, and building Christian character based on biblical values. Effective development is carried out through discipleship, mentoring, small groups, Christian ethics education, Bible-based digital literacy, and the exemplary leadership of church leaders. Therefore, church member development not only functions to nurture the personal spirituality of congregants but also serves as a means of moral and social transformation, enabling believers to live as the light and salt of the world amid social change and the advancement of modern technology.